SPORTS NUTRITION FOR YOUNG ADULTS : A Game-Winning Guide to Maximize Performance - Slomin, Jackie (Callisto Publishing LLC, 2020)
Elevate your diet, elevate your performance--a cookbook and sports nutrition guide for athletes ages 16 and up A structured and disciplined training regimen is vital to any up-and-coming athlete--but without proper nutrition, you are just spinning your wheels